Laser multifunctional fabrication of metallic microthermal components embedded in fused silica for microfluidic applications. (December 2021) - Li, Xiaolong; Xu, Jian; Zhang, Aodong; Peng, Huaiyu; Zhang, Jie; Li, Yucen; Hu, Ming; Lin, Zijie; Song, Yunpeng; Chu, Wei; Wang, Zhenhua; Cheng, Ya
Highlights: Metallic microthermal components embedded in fused silica glass have been fabricated. Localized manipulation and in-situ detection of temperature have been demonstrated. Precise control of temperature in glass microfluidic channels have been realized. Abstract: Microheaters as tiny in-situ heating elements are of great importance for developing many thermal-sensitive microdevice applications. A facile technique for the fabrication of embedded metallic microheaters, microheater arrays, and microthermal sensors based on the combination of femtosecond laser-assisted chemical etching, electroless plating, and mechanical polishing has been proposed. With the proposed technique, uniform and controllable temperature distributions in the central area of fabricated microheaters have been achieved. Moreover, flexible manipulation of localized temperature in a microheater array as well as precise calibration of microheaters based on a simultaneously integrated microthermal sensor has been demonstrated. Furthermore, precise control of temperature in glass channels and acceleration of a chemical reaction in microfluidics using monolithically integrated microheaters have been realized, showing great potential for developing laser manufacturing of multifunctional thermal-control microfluidic devices.